An Aphakic Eye with Two Lenses (A Rare Case Report) - Manpreet Kaur Walia; Aseem Mehta; Amulya (GMC Patiala Journal of Research and Medical Education, 2021)
Aphakia is a condition in which crystalline lens of eye is not present in its normal position of pupillary area. Here we present a case of 27 year old male with decrease in vision in the right eye. On examination it was found that patient is aphakia and on B- scan it was seen that patient was having two lenses in the vitreous.